Hustling, cycling, peacebuilding: Narrating postwar reintegration through livelihood in Liberia - McMullin, Jaremey R. (Review of international studies, 2022)
Ex-combatant youth originated the commercial motorcycling sector in Liberia and have played a dominant role in its development. This article collates key insights narrated by one of Liberia's young ex-combatants-turned-commercial motorcyclists, Edwin Nyankoon, to build narrative accounts of peacebuilding around conceptualisation of youth livelihood, identity, and politics after war. The article contributes to diverse literatures on youth agency by emphasising the need for narrative and subject-led methodologies that anchor research questions and data analysis to research participants’ own language and narrated experiences of post war. It applies insights about everyday peace to interpret hustling as bottom-up peacebuilding, in opposition to dominant top-down peacebuilding accounts of ex-combatants. These latter accounts largely fail to see youth actors as peacebuilding agents, constructing them instead as troublemakers and interpreting their livelihood activities in terms of criminality and threat. Additionally, it argues that hustling also constitutes a peacebuilding style. More than a coping strategy or an indicator of peace, hustling-as-peacebuilding-style is performative: relational, embodied, contradictory, and recognisable to its adherents as peace-promoting even if (and arguably because) outsiders construct it as peace-negating. This analysis problematises agency, social relations, gendered identity, and collective security as they relate to ex-combatant and conflict-affected youth during peace processes.